ISOLASI DAN UJI TOKSISITAS METABOLIT SEKUNDER EKSTRAK n-HEKSANA KULIT BATANG TUMBUHAN Polyalthia pulchra var. angustifolia King (ANNONACEAE) - Yuhendri '; Jasril '; Yuharmen ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The secondary metabolites of the stem bark of Polyalthia pulchra were isolated andthan their toxicity activity assayed using Brine Shrimp Lethality Test (BSLT) method.The sample was extracted by maceration method using n-hexane solvent. Structures ofthe isolated compounds were conducted using Gas Chromatography and MassSpectrometry (GC-MS). The dried sample produced 3.21 g n-hexane extract (0.25%)and 0.032 g 2 nd fraction of n-hexane (FH2) (0.0025%). The toxicity assay showed thatn-hexane extract and FH2 fraction was toxic with LC 50 5.9 and 7.1 ppm. From theresults of GC–MS analysis, it is shown that FH2 fraction contains campesterol,stigmasterol, and γ-sitosterol compounds with retention times 75.605, 76.568 and,78.172 minutes, respectively.